Pattern, Presentation and Management of Marjolin’s ulcer in OmdurmanTeaching Hospital - Rahamah, Abdallah Abdelrhman; Ahmed, Osama Murtada (Gezira Journal of Health Sciences, 2015)
Background : Marjolin’s ulcer is a rare but highly aggressive squamous cell cancer that is most often associatedwith chronic burn wounds.It is the worst complication that victims surviving burn injuries suffer from, but it can be prevented by proper initial management of burn injuries. There was no enough data about this condition in Sudan. Objectives: This study was conducted to study the presentation, causes, latency period, frequency, and management of Marjolin’s ulcer in our local setting in Omdurman teaching hospital. Patients and Methods: This is a prospective cross sectional hospital based study that has been investigating the patients of Marjolin’s ulcer seen at plastic and reconstructive surgery in Omdurman teaching hospital. The study was conducted during the period from May 2010 to January 2013. A special patient data sheet was designed for data collection. Data was analyzed and presented graphically using Statistical Package for Social Sciences (SPSS) software. Results: During this period, 65 cases of Marjolin’s ulcer were included in this study, 44 (67.7%) of them were males and 21 (32.3 %) were females. Male to female ratio is 2.1:1. The mean age was 48 years ± 14.7. With regard to the distribution of the study population by geographical areas, 37 (56.9 %) of them were residing in rural areas and 28 (43.1 %) in urban areas. 25 (38.5 %) of them were farmers and 17 (26.2 %) were house wifes. Chronic un-healed ulcer was the presentation of all patients. Burn was the cause of ulcer in 43 (66.2 %) of the patients, followed by trauma 15 (23.1 %), and infection 7 (10.8 %). Flame burn represented 34 (52.3 %) of cases (p = .000). Concerning the management of the primary cause of the ulcer 44 (67.7 %) were managed in a hospital either by dressing or surgery, while 21 (32.3 %) were managed at home by dressing. The lower limbs were the common site of Marjolin’s ulcer 47 (73.3 %), followed by the upper limbs 10 (15.4 %).The mean ulcer duration (latency period) was 25.96 years ± 8.59. 8 (12.3 %) of the patients has regional lymph nodes involvement all of them were offered lymph nodes dissection.All patients underwent surgery, 43 (66.2 %) underwent excision of the ulcer and split thickness skin grafting, 14 (21.5 %) excision and flap, and 8 (12.3 %) underwent limb amputation. The commonest histological type was squamous cell carcinoma (SCC) 63 (96.9 %). Conclusion: Marjolin’s ulcers are not uncommon in our setting and commonly occur in burn scars due to deep burn that were not skin grafted and were left to heal secondarily; In general this disorder is rarely diagnosed although its etiology is well known; and most of the patients presents late when the disease is already in advanced stages.